1999
DOI: 10.2337/diabetes.48.5.1113
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased intramyocellular lipid content with insulin resistance in lean nondiabetic offspring of type 2 diabetic subjects.

Abstract: Insulin resistance plays an important role in the pathogenesis of type 2 diabetes; however, the multiple mechanisms causing insulin resistance are not yet fully understood. The aim of this study was to explore the possible contribution of intramyocellular lipid content in the pathogenesis of skeletal muscle insulin resistance. We compared insulin-resistant and insulin-sensitive subjects. To meet stringent matching criteria for other known confounders of insulin resistance, these individuals were selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
430
6
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(486 citation statements)
references
References 16 publications
38
430
6
6
Order By: Relevance
“…The observation of increased IMCL in insulin-resistant subjects (10)(11)(12)(13)(14) supported the hypothesis of a possible role of IMCL in the pathogenesis of skeletal muscle insulin resistance and type 2 diabetes mellitus. The possibility of studying this important relation noninvasively and with high accuracy [coefficient of variation as low as about 6% (2)] boosted interest in 1 H-MRS studies on IMCL and the number of succeeding publications considerably (15)(16)(17)(18)(19).…”
Section: Relation Between Imcl Content and Insulin Sensitivitysupporting
confidence: 56%
See 2 more Smart Citations
“…The observation of increased IMCL in insulin-resistant subjects (10)(11)(12)(13)(14) supported the hypothesis of a possible role of IMCL in the pathogenesis of skeletal muscle insulin resistance and type 2 diabetes mellitus. The possibility of studying this important relation noninvasively and with high accuracy [coefficient of variation as low as about 6% (2)] boosted interest in 1 H-MRS studies on IMCL and the number of succeeding publications considerably (15)(16)(17)(18)(19).…”
Section: Relation Between Imcl Content and Insulin Sensitivitysupporting
confidence: 56%
“…the higher the IMCL content, the lower the glucose metabolic clearance rate (12). Several other studies also showed an association between IMCL accumulation and insulin resistance; however, there were also contradictory details: Krššák et al studied a group of normal-weight nondiabetic adults without family history of diabetes and found significant negative correlation between IMCL of soleus muscle and insulin sensitivity, but no relation between IMCL and BMI, age and fasting plasma concentrations of triglycerides (13).…”
Section: Relation Between Imcl Content and Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…7,19,20 The role of IMCL in diabetes is not fully understood, however, an inverse correlation of IMCL levels and insulin sensitivity has been observed by several groups. [21][22][23][24] Figure 3. Orientation dependence of the 1 H-MR spectrum of human muscle.…”
Section: Susceptibility Effects: Separation Of Imcl and Emclmentioning
confidence: 99%
“…Numerous studies have reported the association between elevated plasma NEFA concentrations, intramyocellular triacylglycerol (IMTG, often also abbreviated to IMCL) accumulation and the development of insulin resistance and/or type 2 diabetes [1][2][3][4][5][6][7]. The Randle (glucose-fatty acid) cycle has often been used to explain the mechanism behind skeletal muscle insulin resistance induced by fatty acid (FA) [8].…”
Section: Introductionmentioning
confidence: 99%